Divine Action: Expected and Unexpected - Berry, R. J. 1934-2018 (2002)
Miracles are signs of God's power. Confusion about them comes from misunderstanding or doubting the relationship between God and creation rather than from science properly understood.
Keywords: Providence; Miracles; David Hume; God of the gaps; complementarity